Determination of Acetyl Salicylic Acid in Aspirin tablets - Lana Mohammed Ali; Mariwan Abdulla Hama Salih; Omed Ismael Hayder (Kurdistan Journal of Applied Research)
Drug analysis is an important method for determination of active components of any therapeutic drugs. HPLC, Spectrometry, Direct titration and Back-titration are common effective techniques in drug analysis. They were used in this study in a comparative way for the determination of the correct amount of acetyl salicylic acid in aspirin formulations. The aim of this study is to analysis of aspirin and compares both Direct titration and Back-titration techniques to the standard HPLC technique in order to find alternative, the easy and cheaper procedure to assess the quality of active components of medications aspirin in particular in Sulaimani city. Additionally, Spectrophotometric technique were also used and compared with the standard HPLC method. The samples were collected from different local drug stores in which distribute medications to pharmacies and they were from different companies. The analyses were performed after preparing a solution from each of the samples with a standard solutions for titration procedures. Both direct and back-titration techniques were used to find the concentration of active components in aspirin samples then compared with the data from standard HPLC as a reference value. The study showed that those companies which provide medications to this region were used a standard amount of acetyl salicylic acid in aspirin tablets. The result from Spectrophotometric method showed more accurate than both direct and indirect titration when compared to the reference value from standard HPLC technique due to the high rate of accuracy and precision of this method. However, the result also showed some inconsistent data in terms of the back titration compared to direct titration due to the inaccuracy in back titration. This study concluded with the necessity for quality control to use all these techniques for monitoring all medications which interring this region.